Analisis Kinerja Sumber Daya Manusia Pada Proyek Trans Studio Mall Makassar - Jerianus Tanning; Junus Mara; Helen Adry Irene Sopacua (Paulus Civil Engineering Journal, 2022)
This observation was carried out in order to obtain data on the advantages of labor productivity and labor product (SNI). Human resources to the performance of project implementation and to obtain factors to establish the quality of such human resources. Primary data collection in the form of data taken in the field is data on the number of artisans and the production of handymen every day. The handyman who took the data was only 4 people. Secondary data were obtained from the drawings of the tidying work plan to compare the product of the field labor and the labor product of the labor force (SNI). The results of the study stated that field products increased by 3% compared to the SNI that had been carried out at the Trans Studio Mall Makassar Development Project, it can be concluded that labor productivity in column-fixing work is more productive.